2019
DOI: 10.1007/s00431-019-03408-6
|View full text |Cite
|
Sign up to set email alerts
|

Genotype and phenotype analysis of a cohort of patients with congenital hyperinsulinism based on DOPA-PET CT scanning

Abstract: Congenital hyperinsulinism (CHI) is a clinically, genetically, and morphologically heterogeneous disorder. 18 F DOPA-PET CT scanning greatly improves its clinical outcome. Here, we presented the first Chinese 18 F DOPA-PET CT scanning–based CHI cohort highlighting the variable ethic clinical phenotypes and genotypes. Fifty CHI patients were recruited. Median age at presentation was 2 days. Median fasting time was 2 h. Mean insulin level was 25.6 μIU/ml. Fifty-two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
0
10
0
3
Order By: Relevance
“…Limited histopathological data is provided, and this report predated our understanding of the genetic and molecular mechanisms responsible for congenital HI. Since then, Ni et al described a patient with a KCNJ11 mutation found to have one focal lesion in the pancreatic head and another in the pancreatic body (11). Our group previously reported two separate cases, one suspected and one confirmed, of focal HI in which there were both pancreatic and ectopic intestinal focal lesions (10,12).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Limited histopathological data is provided, and this report predated our understanding of the genetic and molecular mechanisms responsible for congenital HI. Since then, Ni et al described a patient with a KCNJ11 mutation found to have one focal lesion in the pancreatic head and another in the pancreatic body (11). Our group previously reported two separate cases, one suspected and one confirmed, of focal HI in which there were both pancreatic and ectopic intestinal focal lesions (10,12).…”
Section: Discussionmentioning
confidence: 81%
“…Owing to the mechanism of focal lesion development, the occurrence of multiple focal lesions is exceedingly rare. Few cases of HI with multiple focal lesions have been reported to date (8)(9)(10)(11)(12). Of these reports, only one included molecular genetic information confirming that the two lesions, one pancreatic and one ectopic, arose from independent somatic events (8).…”
Section: Introductionmentioning
confidence: 99%
“…Even if nonsense-mediated mRNA decay was involved in the variant, it would not directly explain the cause of the clinical heterogeneity among the three cases. 17,19,20 Moreover, methylation analysis using the patients' lymphocytes, not pancreatic cells, would be complicated, because it has been reported that tissue-specific regulatory elements are strongly associated with tissue-specific differentially methylated regions. 21 To decipher the precise mechanisms underlying the heterogeneity of CHI, accumulating cases and further robust approaches, such as generating pancreatic beta cells from iPS cells of the patients, are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Although those experiments could add some information to our study, we presume that their impact would be limited, because the purpose of our analyses was to elucidate the clinical pathophysiology, especially heterogeneity, among the three cases. Even if nonsense‐mediated mRNA decay was involved in the variant, it would not directly explain the cause of the clinical heterogeneity among the three cases 17,19,20 . Moreover, methylation analysis using the patients’ lymphocytes, not pancreatic cells, would be complicated, because it has been reported that tissue‐specific regulatory elements are strongly associated with tissue‐specific differentially methylated regions 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The following parameters were used to validate the diagnosis: elevated serum concentrations of insulin and C-peptide when blood glucose levels were <2.6 mmol/L; reduced serum levels of β-hydroxybutyrate, acetoacetic acid and FFAs; a glucose infusion rate >8 mg/kg/min to maintain euglycemia; a blood glucose increase >1.5 mmol/L after an injection of glucagon; and positive 18 F-DOPA PET scan results ( 17 ). Due to domestic technical unavailability, 50 of the 74 HH patients received 18 F-DOPA PET scan to confirm pancreas lesions starting in 2017 ( 18 20 ). For KH cases, we also examined charts for evidence of elevated urine ketones or serum β-hydroxybutyrate at the time of hypoglycemia to validate the diagnosis.…”
Section: Methodsmentioning
confidence: 99%